Oil market factors as a source of commonality in liquidity in international equity markets - Abdulrahman Alhassan; Atsuyuki Naka; Abdullah Noman (Journal of Risk and Financial Management, 2021)
When stock markets are less liquid or illiquid, investors are expected to require compensation for taking the risk of not being able to sell quickly. Many studies have documented the existence of the co-movements (commonality) of market liquidity in equity markets as a priced factor. The primary objective of this paper is to introduce the oil market as a potential source of commonality in liquidity. We hypothesize that conditions specific to the oil market can contribute to commonality in liquidity affecting both supply-side and demand-side factors because of its importance to the global economy in general. To this aim, a sample of firms is drawn from 50 countries spanning the period from January 1995 to December 2015. We examine two channels that transmit the effect of oil market movements to the liquidity commonality in international equity markets, namely, oil price returns and oil price volatility. Seemingly unrelated regressions (SUR) are utilized to estimate the effect of oil factors on commonality in liquidity. We find that the returns and volatility of oil prices explain the commonality in liquidity in countries with higher integration with oil markets. In addition, we show that the effect of oil volatility is more pronounced for net oil exporters as opposed to net oil importers after controlling for oil sensitivity. These results are robust to controlling for possible sources of commonality in liquidity as found in the literature and alternative estimation specifications.
Keywords: G12; G15; E44; Q02; 330; commonality in liquidity; international equity markets; oil exporting countries; oil market; oil volatility; OPEC; volatility spillover